2008
DOI: 10.1039/b808246d
|View full text |Cite
|
Sign up to set email alerts
|

Melting behavior of water in cylindrical pores: carbon nanotubes and silica glasses

Abstract: We report a study of the effects of confinement in multi-walled carbon nanotubes and mesoporous silica glasses (SBA-15) on the solid structure and melting of both H(2)O and D(2)O ice, using differential scanning calorimetry, dielectric relaxation spectroscopy, and neutron diffraction. Multi-walled nanotubes of 2.4, 3.9 and 10 nm are studied, and the SBA-15 studied has pores of mean diameter 3.9 nm; temperatures ranging from approximately 110 to 290 K were studied. We find that the melting point is depressed re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
48
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 30 publications
8
48
0
Order By: Relevance
“…22 and Jelassi et al 27 show that for water confined in hydrophobic nanopores the liquid states persists to temperatures lower than in bulk and in hydrophilic confinement. These observations are confirmed by X-ray and neutron diffraction 27,28 .…”
Section: Introductionsupporting
confidence: 65%
“…22 and Jelassi et al 27 show that for water confined in hydrophobic nanopores the liquid states persists to temperatures lower than in bulk and in hydrophilic confinement. These observations are confirmed by X-ray and neutron diffraction 27,28 .…”
Section: Introductionsupporting
confidence: 65%
“…One is the pore width H, the latter is the wettability parameter a w , a w ¼ q w e fw r 2 fwD e ff , which is the ratio of the fluid-wall to the fluid-fluid attractive interaction, where D is the inter-layer spacing in the solid and q w is the number of wall atoms per unit area. Our previous results [3,6,[30][31][32] indicate that the critical a w value for Lennard-Jones fluids in smooth-walled pores is about 1, and thus for alpha greater than 1, we have strongly attractive pores-like a wall of graphite, and then occurs an elevation in freezing temperature-while for values of alpha less than 1, we have weakly attractive pores-like a wall of silica, and then occurs a depression in freezing temperature. Our experimental evaluation of the effective wettability parameter a p based on the measurements of contact angle of OMCTS inside the silica pores has shown that the effective value of a in silica pores is about a p = 0.4 [24], and we can expect the depression of the melting temperature for OMCTS in the studied matrices.…”
Section: Discussionmentioning
confidence: 87%
“…For cylindrical pores with lower diameter, the confined phase at low temperature is an inhomogeneous phase with partially crystalline domains interspersed with amorphous regions [19]. For OMCTS in SBA-15 and Al-SBA-15 with pore size about 4 nm, we can expect that inside the pores below the melting temperature rather inhomogeneous phase will be formed, and at the solid phase, the crystal form can be partially deformed [30,31]. In such a case, the solid-solid transition observed in OMCTS bulk does not occur in the pores.…”
Section: Dielectric Relaxation Spectroscopy Resultsmentioning
confidence: 99%
“…A variety of solid surfaces has been considered: silica pores (Vycor glass) [25,26], platinum [27], magnetite [28], zirconia [29], or pure carbon composites (graphite structure) in several geometries, from planar [30][31][32][33][34] to cylindrical [35][36][37]. At the experimental side, many authors have contributed to the study of water at hydrophobic interfaces using a wide variety of techniques such as scanning tunneling microscopy [38], environmental scanning electron microscopy and electron energy loss spectroscopy [39], ultrafast optical Kerr effect spectroscopy [40], atomic force spectroscopy [41], calorimetry [42], neutron diffraction [43][44][45][46] and electron cryomicroscopy [10].…”
Section: Introductionmentioning
confidence: 99%